Implementation of STEM-Based Experiential Learning to Improve Critical Thinking Skills on Ecosystem Materials - Khairati Khairati; Wiwit Artika; Muhammad Ali Sarong; Abdullah Abdullah; Hasanuddin Hasanuddin (Postgraduate, University of Mataram, 2021)
The low critical thinking skills of learners are triggered by less supportive learning. The learning process has not emphasized the development of critical thinking skills, it is because in learning learners tend to memorize concepts so that critical thinking skills are not trained, making learners less active in the learning process and not achieving minimum completion criteria, there needs to be efforts to overcome them. The formulation of the problem in this study is: Is there a significant difference in the improvement of students' critical thinking skills with the implementation of STEM-based Experiential Learning learning in class VII MTsN Aceh Besar? This research aims to find out the significance of differences in improving learners' critical thinking skills with the implementation of STEM-based Experiential Learning learning. The method used in this study is an experimental method with the design of One Group Pretest-Postets design. The population of this study is all students of class VII MTsN Aceh Besar which amounted to 120 learners. The instrument used to measure critical thinking skills using multiple choice questions is 10 questions. Data analysis using the One Simple t-Test test at a significant level of 0.05. The results of the One Simple t-Test test of the students' critical thinking skills were obtained by Sig. (0.00) < (0.05), showed that learners' critical thinking skills were better and there was a significant improvement with the implementation of STEM-based Experiental Learning.